PENGARUH PENGULANGAN PENGGORENGAN TERHADAP KANDUNGAN ASAM LEMAK BEBAS DAN VISKOSITAS MINYAK HASIL PENGGORENGAN: Effect of Repeated Frying Against Free Fatty Acid Content and Viscosity Oil Frying Repeatedly - Sutanto, Saiman; Rahman, Rahmawati; Abriana, Andi (Jurnal Ilmiah Ecosystem, 2016)
Changes that occur chemically and physically on cooking oil used to fry during which in turn will affect the quality of the product is fried. The chemical changes that occur such as free fatty acid, thiobarbituric acid, peroxide; whereas physical changes such as: color, smoke point, viscosity, smell and taste. The resulting chemical changes, namely an increase in free fatty acids and physically namely oil colors become darker, the increase in viscosity and a decrease in smoke point. This study aims to determine the free fatty acid content and viscosity of the oil that has been used repeatedly. The results of this study are expected to produce information about the quality of frying oil that has been used repeatedly, so that it can be seen up to frying how many times the result of frying oil can still be used. Repetition frying can lead to increased free fatty acids in the oil frying and getting repeatedly used the free fatty acid content further increased. Repetition of frying oil used more and the quality has gone downhill since free fatty acid content is higher. The content of free fatty acids in the oil was frying chicken giving a very real difference to the result of frying oil bananas. Repetition pan many times can increase the viscosity of the oil. The viscosity of the oil was frying bananas providea very real difference to the chicken frying oil